Study of neuroprotective factors mediated by Omega 3 and cognitive stimulation against amnesic mild cognitive impairment in patients residents of the city of Córdoba, Argentina - Castro Zamparella, Tatiana (2022)
General description: In older adults, neurodegenerative disease is very prevalent. In Latin American with low economic resources, public health proposals can be based on preventive and educational actions, promoting brain protection factors. Background shows that a diet based on foods rich in essential fatty acids Omega 3 (ω3) contributes to the prevention of neurological clinical diseases. Goal: Explore neuroprotective factors mediated by dietary supplementation (ω3) and cognitive stimulation that could delay amnesic-type cognitive decline and thus, the diagnosis of dementia. Material and Method: Non-probabilistic sample of adults between 60-80 years of age, both sexes, from Córdoba City, Argentina. N=14 divisions in Healthy Control Group (S) and Cognitive Impairment (DC). Prepost evaluation neurocognitive battery and blood lipid profile were made. Treatment with ω3 capsules (1 g) for 24 weeks and cognitive stimulation workshops for 24 weeks. To then exchange and complete 12 months with the other treatment. Results: The groups S:ω3 and S:EC didn´t present changes pre-post treatment. In the DC:ω3 group, maintenance of cognitive function is observed, as in the DC:EC group. Although the performance in the DC groups is lower due to the cognitive condition of the participants, no pre-post treatment changes are observed. The DC:ω3 and DC:EC groups are statistically different from the S:ω3 group. Discussion and conclusions: In clinical practice, it is expected that an older adult with cognitive failures compatible with MCI get worse their performance from one year to the next if the conditions and habits are not modified. The data obtained so far showed a tendency that the intervention sustained for 12 months at the level of external stimulation of cognitive functions and abilities and the adequate nutritional contribution provided by ω3 sustains cognitive performance. Therefore, health trends are focused on prevention and thus provide quality of life to the adult population.